The role of kyai leadership in preventing child marriage tradition to strengthen human resources in Madura - Astutiek, Dwi; Sukesi, Sukesi (Annals of Human Resource Management Research, 2025)
Purpose: Elaborating the leadership role of the kyai. Finding solutions to prevent the tradition of child marriage as an effort to strengthen human resources in Madura through an approach based on government policies and traditional practices in the community. Methodology: Using a descriptive qualitative approach, in-depth interviews with informants and key informants. Using an interview guide. Primary data was collected through in-depth interviews. Data were enriched with observation and review of relevant literature. Results: 1) Public policies are implemented in a structured, systematic and massive manner. 2) The implementation of the policy encountered several obstacles and obstacles related to the tradition of child marriage which is rooted because it is carried out for generations, 3) The role of kyai has the power to help overcome child marriage strategically and systematically, as an effort to help strengthen human resources in Madura. Kyai is very open, willing and easy to accept new knowledge related to the physical and psychological health impacts of child marriage. Conclusions: Kyai is a role model-teacher figure for Madurese people who should be obeyed and followed. The role of kyai leadership is a potential that can answer problems in Madura as an effort to strengthen human resources by not marrying off their children at an early age. Although the tradition of child marriage in Madura is very rooted. Limitations: This research is limited to providing awareness, solutions and proposals for strategic steps that must be taken for structural clerics, cultural clerics, communities and policy makers. Further research is needed regarding the application and evaluation of the implementation of the NU/MUI fatwa in preventing child marriage. Contribution: Contributing to the scientific field for scientists, policy makers, religious leaders and the community: realizing the leadership role of kyai, providing solutions to prevent child marriage. Kyai's fatwa can save the fate of the nation's children, provide access to higher education. This research is the basis for making policies and the next strategic steps.